اثر التسيير دورة الاستغلال في تحسين أداء المالي للمؤسسات - لبنى, بوعزيز; كوثر, مسعودي; بوليفة, ايوب (جامعة الوادي - University of Eloued, 2023)
"تهدف الدراسة إلى معرفة أثر تسير دورة الاستغلال على الأداء المالي للمؤسسات حيث تم الاعتماد علي المنهج الوصفي و التحليلي وقد تم اختيار شركة سوف للدقيق ميدانا للدراسة بالاعتماد علي تحليل جدول حسابات النتائج والميزانية الشركة. وتوصلت الدراسة إلي وجود ارتباط إيجابي بين تسيير دورة الاستغلال والأداء المالي محل الدراسة .كما أنها تتمتع بهامش آمان يمكنها من مواجهة التزاماته في المواعيد استحقاقها ""the study aims to find out the impact of the exploitation cycle on the financial performance of the institutions, where the descriptive and analytical approach was relied upon souf company was selected as a field for the study, based on the analysis of the results table and the company's budget . the study found that there is a positive correlation between the conduct of the exploitation cycle and the financial performance under study. It also has a safety margin that enables it to meet its due date obligations. "
Keywords: التسيير ، دورة الاستغلال ، الأداء المالي ، التحليل المالي; management, exploitation cycle ,financial performance ,financial analysis.